Innovation after Brexit. (1st June 2016) - Kingston, William
Abstract : Brexit is intended to return autonomy for law-making to the UK Parliament, and this opportunity could be used to improve intellectual property laws. These were originally drafted to support innovation, but like other laws of property they were captured by interests. The result is that their original function has been far surpassed in economic importance by their use for moving corporate profits to and through tax havens for tax evasion and avoidance. Although an opportunity to improve information protection laws may indeed result, Britain has never been a leader in drafting these, compared with Germany and the United States. Also, to the extent that better laws could refocus investment on technological innovation, and away from financial innovation, it could be expected that they would be opposed by interests with a major stronghold in the City of London. Reference is made to specific proposals for change already advanced in Prometheus, to which is added a new suggestion about how more generous overhead payments from public funding of innovation could help to stimulate more firms to bid for this. Also, a proposal is made for a means of rectifying a series of legal decisions which have had the effect of denying firms the ability to benefit from new ideas offered by outsiders.